Excellent outcomes after radiotherapy alone for malignant spinal cord compression from myeloma - Rades, Dirk (Radiology and oncology (Ljubljana), 2016)
Uncertainty exists whether patients with spinal cord compression (SCC) from a highly radiosensitive tumor require decompressive spinal surgery in addition to radiotherapy (RT). This study addressed the question by evaluating patients receiving RT alone for SCC from myeloma. Patients and methods. Data of 238 patients were retrospectively analyzed for response to RT and local control of SCC. In addition, the effect of RT on motor function (improvement, no further progression, deterioration) was evaluated. Overall response was defined as improvement or no further progression of motor dysfunction. Prior to RT, patients were presented to a neurosurgeon for evaluation whether upfront decompressive surgery was indicated (e.g. vertebral fracture or unstable spine). Results. In the entire cohort, the overall response rate was 97% (53% improvement plus 44% no further progression). Following RT, 88% of the patients were able to walk. Of the 69 non-ambulatory patients 44 patients (64%) regained the ability to walk. Local control rates at 1, 2 and 3 years were 93%, 82% and 82%, respectively. A trend towards better local control was observed for patients who were ambulatory before starting RT (p = 0.08) and those with a more favorable performance status (p = 0.07). Conclusions. RT alone provided excellent response rates, functional outcomes and local control in patients with SCC from myeloma. These results should be confirmed in a prospective randomized trial.
Keywords: hrbtenjača; mielom; myeloma; radioterapija; radiotherapy; spinal cord compression